2020
DOI: 10.3389/fendo.2020.00288
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose With Comparable Glucose-Lowering but Superior Weight-Loss Efficacy to Dipeptidyl Peptidase-4 Inhibitors: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Acarbose and dipeptidyl peptidase-4 inhibitors (DPP-4is) have several similarities regarding their efficacy. Assessing the hypoglycemic and weight-loss effects, as well as the tolerability between them at their optimal dosages, could provide a better management of adult type 2 diabetics.Methods: We performed a systematic review and network meta-analysis (NMA) on randomized controlled trials that were identified from the databases of EMBASE, MEDLINE, Cochrane Central Register of Controlled Trials, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Moreover, ACA (glucose deprivation inducer) reduced relative body weight compared with the control group. ACA inhibits alpha-amylase and alpha-glucosidase; therefore, delayed absorption of complex carbohydrates from the intestine leads to decreased glucose level and body weight (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACA (glucose deprivation inducer) reduced relative body weight compared with the control group. ACA inhibits alpha-amylase and alpha-glucosidase; therefore, delayed absorption of complex carbohydrates from the intestine leads to decreased glucose level and body weight (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…61 Acarbose inhibits alpha glucosidases at the intestinal brush border, thereby slowing or preventing conversion of disaccharides and polysaccharides into monosaccharides, and is associated with very modest weight loss without alterations in energy intake in patients with diabetes. 62,63 Acarbose also has a role in the management of dumping syndrome after bariatric or foregut surgery. 64,65 The most common adverse effects include abdominal pain, bloating, flatulence, and diarrhea, which likely result from increased colonic fermentation of carbohydrates.…”
Section: Non-fda Approved Medicationsmentioning
confidence: 99%
“… 70 A median weight reduction of 3.5 kg was achieved when acarbose 100 mg three times daily was added to a sulfonylurea in a group of patients with T2DM. 71 When weight loss efficacy was compared between acarbose and DPP-IV inhibitors in a meta-analysis of randomized controlled trials, acarbose demonstrated superiority ( p <0.05). There was a mean difference of −1.23 kg favouring acarbose.…”
Section: Resultsmentioning
confidence: 99%